Reason and Praxis in Spinoza’s Ethics - Rodríguez Quiroz, Gilmar Joel (2022)
With respect to the axes that articulate Spinozian thought, they are summarized in three aspects: It is a metaphysical proposal, since a rational order underlies nature that starts from the idea of God; epistemic, since the intellect can know and identify this order; and ethics because from knowledge, a lifestyle is adopted, based on the effort that will give meaning to moral behavior. In this sense, the purpose of this article will be the role played by the concept of Conatus that would represent the aforementioned effort, around a practical rationality, exposed by Spinoza in the fourth part of his Demonstrated Ethics according to the geometric order, whose theme It lies in the deep link between ontology and morality, since philosophy not only tries to answer the question of what the world is, but also the problem of how we can live better in it.